Predictive Analysis of Financial Statements and Its Role in Achieving Sustainability and Rationalizing Administrative Decisions: An Applied Study - Shaymaa Abdulhusein Abdulkadhim Alisawi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The aim of the study is to delve into the disclosure of future financial statements and its reflection on the sustainability of the banking sector by extrapolating and reporting the pillars of banking sustainability. It adopting a mechanism at a high level in the country to promote data technology and increase support for its resources in order to provide an appropriate structure for the development of the banking and financial sector by providing appropriate information at the right time and expanding the preparation of future studies and research and linking them to many variables that are considered influences faced by the Iraqi financial market in the contemporary business environment for providing a suitable environment in the capital market by supporting the banking and financial sector by means of modern technology and obliging companies within the sectors. The study's goal was accomplished by using the content analysis method for the annual reports of banking units listed in the Iraqi financial market for the years 2020–2023. This was done after developing an indicator to gauge future financial statements' level of disclosure in compliance with the Iraqi Financial Market Law and the disclosure guidelines issued in accordance with it, as well as the fact that the index is being used in the country for the first time. The study draws several conclusions, the most important of which being that , One of the most notable recommendations reached by the study is to require the banking units listed in the Iraqi financial market to display future financial statements in order to ensure the achievement of sustainability supporting the banking sector within the annual reports. The level of disclosure of future financial statements varied in the financial reports of the banking units listed in the Iraqi financial market, where the average disclosure was high with a positive moral relationship to the market financial value.